Status and hotspot analysis of Qingfei Paidu Decoction for the prevention and treatment of COVID-19 based on bibliometric analysis - Zhang, Huifang; Liu, Yang; Shang, Xiyu; Cao, Yuqing; Li, Jiajia; Chen, Guangkun; Ji, Xinyu; Zhang, Lei; Fan, Yipin; Ma, Yan (Frontiers in Pharmacology, 2024)
Background: Qingfei Paidu Decoction (QFPDD) has played an important role in the prevention and treatment of COVID-19 infection in China. The present study aims to perform an econometric analysis and visualization of the literature on the treatment of COVID-19 with QFPDD in the Chinese databases and English databases. Methods: Six databases including such as Chinese databases CNKI, VIP, CBM, WANFANG as well as English databases PubMed, Web of Science were searched for publications related to the prevention and treatment of COVID-19 with QFPDD. The institutions, authors, keywords of each publication were cisualized using the software of CiteSpace. Results: A total of 187 literatures on the prevention and treatment of novel coronavirus infection with QFPDD were included, of which 145 (77.5%) were in Chinese and 42 (22.5%) were in English. Those publications were written by 926 authors from 383 institutions. There were 78 theoretical studies (41.7%), 63 clinical studies (33.7%), and 46 basic studies (24.6%). The cooperative institutions with the core of "Institute of Clinical Basic Medicine of Chinese Medicine, China Academy of Chinese Medicine" and "Shanghai University of Chinese Medicine Cross Academy of Science" have been formed, and two core teams with "Wang Yanping" and "Zhang Weidong" have been formed. The keyword analysis showed that the research mainly focuses on pathologic pathogenesis, clinical efficacy, adverse reactions, integrated Chinese and western medicine therapy, network pharmacology research. Conclusion: QFPDD has attracted worldwide attention, mechanism research and clinical research may become a future development trend. Therefore, in-depth basic research and clinical studies with large samples and multi-center cooperation should be carried out to provide high-level evidence-based evidence for the prevention and treatment of COVID-19 with QFPDD.